Pengaruh Pendekatan Realistic Mathematics Education (RME) Pada Hasil Belajar Siswa Di Kelas III SDN Gandekan Surakarta Pada Muatan Pelajaran Matematika - ., Agnes Mariana Setia Dewi; ., Anggit Grahito Wicaksono; ., Jumanto (Jurnal Pendidikan, Sains Dan Teknologi, 2023)
The purpose of this research is to find out whether or not there is an effect of the Realistic Mathematics Education (RME) approach on student learning outcomes in class III SDN Gandekan Surakarta mathematics content in the 2021/2022 academic year. This research is a quantitative study with a one group pretest posttest design. The population in this study were 28 students. The sample used was all members of the population. The technique used was saturated sampling technique. Data collection techniques were such as test, observations, intervuews, and documentation. In this study, to test the instrument validity test, reliability test, discriminating power, and level of difficulty were used. The data analysis technique in this study was Shapiro Wilk’s normality analysis and hypothesis testing using the Wilcoxon test. Based on the analysis of statistical data with the help of SPSS version 25, the average value data obtained before the treatment was applied was 54.82. After applying the treatment, the result was 66.25. The result of the Asymp. Sig (2-tailed) paired sample t-test was 0.000, which meant 0.000 <0.05. Thus, the hypothesis that ‘there is a significant effect of the Realistic Mathematics Education (RME) approach on student learning outcomes in class III SDN Gandekan Surakarta in the mathematics content in the 2021/2022 academic year’ is acceptable.